Comparative study of two training methods in the preparation of Athletics pitchers force of Granma province, during the pre-competitive - Peña Fernández, Juan Miguel (Revista Universidad de Guayaquil, 2010)
This work is the result of the author’s doctoral thesis was defended at the Universidad de la Palmas de Gran Canaria in Spain, to get a PhD in Science of Physical Culture and sport it is expressed, the results the study of the combination of two methods of progression of the charges for the preparationof athletic strength of the pitching categories during the pre school competitive, where the most effective combination is the undulating plateau, and that allows athletes these categories improvedrecovery from the physiological point of view, and shows an improvement in the indicators of generalphysical and special physical preparation, which confirms the hypothesis in research
Keywords: Method; strength; training; preparation; loading